Les Prix littéraires du Gouverneur général du Canada : une bibliographie - Irvine, A. D.; Rivère, Edmond; Tolman, Stephanie (University of Ottawa Press, 2018)
This authoritative bibliography of Canada's premier literary prize, the Governor General's Literary Awards, offers a comprehensive and in-depth look at the Awards and its celebrated authors.